2021
DOI: 10.1002/hbm.25702
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated anterior insula reactivity as robust functional biomarker for chronic pain—Meta‐analytic evidence from neuroimaging studies

Abstract: Neurobiological pain models propose that chronic pain is accompanied by neurofunctional changes that mediate pain processing dysfunctions. In contrast, meta‐analyses of neuroimaging studies in chronic pain conditions have not revealed convergent evidence for robust alterations during experimental pain induction. Against this background, the present neuroimaging meta‐analysis combined three different meta‐analytic approaches with stringent study selection criteria for case–control functional magnetic resonance … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 53 publications
2
22
0
Order By: Relevance
“…Indeed, the large-scale activation following modality PEs and unsigned intensity PEs themselves does not correspond to any single network description, but seems to involve all of the above; possibly, different dynamics are at play over the course of the stimulation, which do not allow for the disentangling of single networks. In fact, recent meta-analytic evidence of resting-state functional connectivity points to the existence of a pain-related network centered on the anterior insula [ 50 ]. The activation associated with both pain-related (posterior insula) activation and that associated with PE-related (anterior insula) activation correspond well with connectivity gradients observed along the posterior–anterior axis [ 51 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the large-scale activation following modality PEs and unsigned intensity PEs themselves does not correspond to any single network description, but seems to involve all of the above; possibly, different dynamics are at play over the course of the stimulation, which do not allow for the disentangling of single networks. In fact, recent meta-analytic evidence of resting-state functional connectivity points to the existence of a pain-related network centered on the anterior insula [ 50 ]. The activation associated with both pain-related (posterior insula) activation and that associated with PE-related (anterior insula) activation correspond well with connectivity gradients observed along the posterior–anterior axis [ 51 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal data from both sources are the basis for reinforcement learning and further enhance our understanding of the functional synergies within the insula. Importantly, pathological learning mechanisms [ 1 , 9 ] and abnormalities in anterior insula-related function have been reported in chronic pain [ 50 , 66 ]. Our data therefore offers the possibility that a misrepresentation of PEs constitutes a potential mechanism in pain persistence.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal data from both sources are the basis for reinforcement learning and further enhance our understanding of the functional synergies within the insula. Importantly, pathological learning mechanisms [1,9] and abnormalities in anterior insula-related function have been reported in chronic pain [40,51]. Our data therefore offers the possibility that a misrepresentation of PEs constitutes a potential mechanism in pain persistence.…”
Section: Discussionmentioning
confidence: 55%
“…Indeed, the large-scale activation following modality PEs and unsigned intensity PEs themselves does not correspond to any single network description, but seems to involve all of the above; possibly, different dynamics are at play over the course of the stimulation, which do not allow for the disentangling of single networks. In fact, recent meta-analytic evidence of resting-state functional connectivity points to the existence of a pain-related network centered on the anterior insula [40]. The activation associated with both pain-related (posterior insula) activation, and that associated with PE-related (anterior insula) activation correspond well with connectivity gradients observed along the posterior-anterior axis [41][42][43].…”
Section: Discussionmentioning
confidence: 82%
“…Our finding that the bilateral dorsal anterior insular cortex is involved in the modulation of both autonomic systems during all task types supports the hypothesis that these regions are fundamental hubs of CAN. This finding, coupled with the evidence that the functional network supporting CAN is at least partially anchored in the salience network is supported by evidence from different lines of research such that a long tradition of animal and human studies has shown the anterior insular cortex is a critical viscerosensory area, being the primary site of cortical interoceptive projection and strongly involved in interoceptive processing and interoceptive dysregulations (Arthur D Craig, 2003;Arthur D Craig & Craig, 2009b;Ferraro et al, 2021;Foxe & Schroeder, 2005;Li et al, 2018;Uddin, 2014;Xu et al, 2020;Xue Hai, 2016). One of the primary functions of this region, and aligning with its involvement in a wide range of conditions and behaviors (Arthur D Craig & Craig, 2009a; Uddin, 2014), appears to be the integration of external information with the internal state of the body (interoception)…”
Section: Discussionmentioning
confidence: 81%